A new phenylethanoid glycoside from Incarvillea compacta. Issue 6 (2nd June 2016) - Wu, Hai-Feng; Zhu, Yin-Di; Zhang, Li-Jing; Zou, Qiong-Yu; Chen, Li; Shen, Ting; Wang, Xin-Feng; Ma, Guo-Xu; Hu, Bo-Ran; Hu, Wei-Cheng; Xu, Xu-Dong
Abstract: A new phenylethanoid glycoside, 3′′′- O -methylcampneoside I (1 ), was isolated from the 90% ethanolic extract of the roots of Incarvillea compacta, together with three known compounds, campneoside I (2 ), ilicifolioside A (3 ), and campneoside II (4 ). Their structures were determined spectroscopically and compared with previously reported spectral data. Compound1 existed as epimers and displayed better 1, 1-diphenyl-2-picrylhydrazyl (DPPH)-free radical scavenging activity using di- tert -butyl-4-methylphenol (BHT) as the positive control. In addition, pretreatment of human HepG2 cells with compound1 significantly increased the viability on CCl4 -induced cell death.